STUDENTS’ LEARNING STYLE IN STUDYING VOCABULARY AT EIGHTH GRADE STUDENTS OF SMP SWASTA BUDISATRYA MEDAN - Dina Azizah Lubis; Anni Holila Pulungan; Yeni Erlita (Universitas Negeri Medan, 2017)
The study discusses about Students Learning Style in Studying Vocabulary at Eighth Grade Students of SMP Swasta Budisatrya Medan. The objective of the study is to investigate type of students learning style in studying vocabulary and to analyze how is the VARK learning style applied in studying vocabulary at eighth grade students of SMP Swasta Budisatrya Medan in academic year 2016/2017. There were 38 students in the class of VIII-1 as the subject of this research. This study was conducted by using qualitative research. In this study, the researcher collected the data by using questionnaire and observation task sheet. The questionnaire designed by Fleming (2001). The result showed that the type of students learning style was Visual (15.7%), Aural (18.4%), Read/ Write (55.2%), and Kinesthetic (10.5%). It means that there was 6 of 38 students was visual preference, 7 of 38 students was aural preference, 21of 38 students was read/ write and 4 of 38 students was kinesthetic. The result of the data showed that VARK model was very helpful in teaching learning process especially in studying vocabulary. Keywords: Learning Style, VARK, Vocabulary.